Employee Reward: A Systematic Literature Review - Anistuti, Fri; Sopiah, Sopiah (Jurnal Etnik: Ekonomi-Teknik, 2022)
Discussion regarding employee rewards is very important in the management of human resource management. This study aims to review studies that discuss employee rewards. The data used is 32 with 2 Scopus databases using the Publish or Perish and Taylor and Francis applications in the 2017-2022 period. The analysis technique used is Prisma and bibliometric analysis using VOSviewer software. The results of the analysis show that the topic of employee rewards is related to the topic of motivation and productivity which is visualized through Co-Authorship and Co-Occurrence. This literature study is expected to be a reference for further research on employee rewards.